Stress Detection of Children With ASD Using Physiological Signals - Sevgi Nur Bilgin Aktaş; Pınar Uluer; Buket Coşkun; Elif Toprak; Duygun Erol Barkana; Hatice Köse; Tatjana Zorchec; Ben Robins; Agnieszka Landowska (IEEE, 2022)
This paper proposes a physiological signal-based stress detection approach for children with autism spectrum disorder (ASD) to be used in social and assistive robot intervention. Electrodermal activity (EDA) and blood volume pulse (BVP) signals are collected with an E4 smart wristband from children with ASD in different countries. The peak count and signal amplitude features are derived from EDA signal and used in order to detect the stress of children based on the previously provided reference baselines. Furthermore, a comparison has been made with the stress values determined using low frequency (LF) and high frequency (HF) values extracted from BVP signal.
Keywords: physiological signals; child-robot interaction; autism; stress